Photoproduction models for total cross section and shower development - Cornet, Fernando (2015)
A model for the total photoproduction cross section, based on the ansatz that resummation of infrared gluons limits the rise induced by QCD minijets in all the total cross-sections, is used to simulate extended air showers initiated by cosmic rays with the AIRES simulation program. The impact on common shower observables, especially those related with muon production, is analysed and compared with the corresponding results obtained with previous photoproduction models.